Pentingnya Pelayanan Konseling Pastoral: Menjembatani Iman Dan Kehidupan Gereja Dan Masyarakat - Napitupulu, Anggi Hani Ruth (Sekolah Tinggi Diakones HKBP, 2024)
Nowadays, the lives of congregations and communities are increasingly immersed in the glitz of modernity that upholds individualistic life. This era has brought human life into a very fast flow, full of various challenges waiting to be resolved. In the church environment, congregations often face various personal, family, and relationship problems that affect their lives holistically. The same thing is experienced by society, which is also struggling with emotional and spiritual crises such as depression, intrapersonal conflict, and loss of motivation to live. To overcome this crisis, pastoral counseling plays an important role in connecting the congregation's faith with the reality of their lives. Using a literature review method, this study examines the role of pastoral counseling in providing emotional and spiritual support to individuals, as well as overcoming various challenges of daily life through Christian teachings. The results of the study indicate that pastoral counseling not only strengthens spiritual bonds within the church but also creates a more harmonious relationship between the church and society. Through an approach based on love and understanding, pastoral counseling helps individuals deal with problems such as anxiety, depression, and social conflict, thus providing a positive impact on the quality of life of the congregation and society.